Extreme Heat and COVID-19: A Dual Burden for Farmworkers - López-Carr, David; Vanos, Jennifer; Sánchez-Vargas, Armando; Vargas, Río; Castillo, Federico (Frontiers in Public Health, 2022)
Currently, there is an extensive literature examining heat impacts on labor productivity and health, as well as a recent surge in research around COVID-19. However, to our knowledge, no research to date examines the dual burden of COVID-19 and extreme heat on labor productivity and laborers’ health and livelihoods. To close this research gap and shed light on a critical health and livelihood issue affecting a vulnerable population, we urge researchers to study the two topics in tandem. Because farmworkers have a high incidence of COVID-19 infections and a low rate of inoculation, they will be among those who suffer most from this dual burden. In this paper, we discuss impacts from extreme heat and COVID-19 on farm laborers. We provide examples from the literature and a conceptual framework showing the bi-directional nature of heat impacts on COVID-19 and vice versa. We conclude with questions for further research and with specific policy recommendations to alleviate this dual burden. If implemented, these policies would enhance the well-being of farmworkers through improved unemployment benefits, updated regulations, and consistent implementation of outdoor labor regulations. Additionally, policies for farmworker-related health needs and cultural aspects of policy implementation and farmworker outreach are needed. These and related policies could potentially reduce the dual burden of COVID-19 and extreme heat impacts while future research explores their relative cost-effectiveness.